The origin(s) and geodynamic significance of Archaean ultramafic-mafic bodies in the mainland Lewisian Gneiss Complex, North Atlantic Craton - Guice, G; McDonald, I; Hughes, H; MacDonald, J; Faithfull, J (Journal of the Geological Society, 2020)
This is the author accepted manuscript. The final version is available from the Geological Society via the DOI in this record The geodynamic regime(s) that predominated during the Archaean remains controversial, with the plethora of competing models largely informed by felsic lithologies. Ultramafic-mafic rocks displaying distinctive geochemical signatures are formed in a range of Phanerozoic geotectonic environments. These rocks have high melting points, making them potentially useful tools for investigating Archaean geodynamic processes in highly metamorphosed regions. We present field mapping, petrography, traditional bulk-rock geochemistry, and platinum-group element geochemistry for 12 ultramafic-mafic bodies in the Lewisian Gneiss Complex (LGC), which is a highly metamorphosed fragment of the North Atlantic Craton in northwest Scotland. Our data indicate that most of these occurrences are layered intrusions emplaced into the tonalite-trondhjemitegranodiorite (TTG)-dominated crust prior to polyphase metamorphism, representing a significant reevaluation of the LGC’s magmatic evolution. Of the others, two remain ambiguous, but one (Loch an Daimh Mor) has some geochemical affinity with abyssal/orogenic peridotites and may represent a fragment of Archaean mantle, although further investigation is required. The ultramafic-mafic bodies in the LGC thus represent more than one type of event/process. Compared with the TTG host rocks, these lithologies may preserve evidence of protolith origin(s), with potential to illuminate tectonic setting(s) and geodynamic regimes of the early Earth.